Fabrication of microchannels through template-based electrophoretically assisted micro-ultrasonic machining - Lian, Haishan; Deng, Cuiyuan; Zhang, Linpeng; Mo, Yuandong; He, Junfeng; Guo, Zhongning (International journal of advanced manufacturing technology, 2023)
Silicon, glass, and other hard and brittle materials exhibit strong inertness and chemical stability and are ideal substrates for preparing macrochannels. To prepare microchannels with hard and brittle material through high-precision and high-efficiency machining, the author innovatively proposed a new technology called template-based electrophoretically assisted micro-ultrasonic machining (TBEPAMUSM). The microchannel shape punch-pin was transferred to a workpiece by micro-ultrasonic machining (MUSM). Due to the electrophoretic characteristics of ultrafine abrasive particles, applying a DC field can ensure that ultrafine abrasive particles are present in the machining area. Four process parameter (average particle size, particle concentration, ultrasonic power, and electrophoretic DC voltage) single-factor experiments and orthogonal experiments were carried out for TBEPAMUSM. The single-factor experimental study indicated that (1) an increase in the average particle size and ultrasonic power can effectively improve the material removal rate (MRR), but the surface roughness (SR) also decreases. (2) An increase in the abrasive concentration reduces the SR, but a suitable concentration can maximize the MRR. (3) When a suitable DC voltage is introduced, the MRR and SR can be effectively improved. The orthogonal experiment results show that the average particle size exerts the greatest effect on the SR and MRR. Considering the balance between machining quality and machining efficiency, the optimal parameters were as follows: ultrasonic power 70%, average abrasive particle size 18 μm, abrasive concentration 18%, and DC voltage 40 V.